2000
DOI: 10.1016/s0896-6273(00)00126-4
|View full text |Cite
|
Sign up to set email alerts
|

Subunit Composition of Kainate Receptors in Hippocampal Interneurons

Abstract: Kainate receptor activation affects GABAergic inhibition in the hippocampus by mechanisms that are thought to involve the GluR5 subunit. We report that disruption of the GluR5 subunit gene does not cause the loss of functional KARs in CA1 interneurons, nor does it prevent kainate-induced inhibition of evoked GABAergic synaptic transmission onto CA1 pyramidal cells. However, KAR function is abolished in mice lacking both GluR5 and GluR6 subunits, indicating that KARs in CA1 stratum radiatum interneurons are het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
189
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(207 citation statements)
references
References 40 publications
15
189
3
Order By: Relevance
“…In addition, it has also been shown that activating receptors incorporating the GluR5 subunit results in a reduction of g-aminobutyric acid (GABA) inhibitory synaptic transmission (Clarke et al, 1997), an effect that is again reversed by the administration of a GluR5-preferring antagonist. Given that kainate can still block hippocampal GABAergic transmission in GluR5 knockout mice, it would appear that the GluR5 is not the only subunit involved in kainite-mediated GABA interactions (Mulle et al, 2000), suggesting that heteromeric rather than homomeric receptors are required for this process. Projecting these data to the human cortex, the decrease in kainate receptors in schizophrenia containing the GluR5 subunit would likely affect the 'fine-tuning' of both inhibitory and excitatory synaptic transmission in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has also been shown that activating receptors incorporating the GluR5 subunit results in a reduction of g-aminobutyric acid (GABA) inhibitory synaptic transmission (Clarke et al, 1997), an effect that is again reversed by the administration of a GluR5-preferring antagonist. Given that kainate can still block hippocampal GABAergic transmission in GluR5 knockout mice, it would appear that the GluR5 is not the only subunit involved in kainite-mediated GABA interactions (Mulle et al, 2000), suggesting that heteromeric rather than homomeric receptors are required for this process. Projecting these data to the human cortex, the decrease in kainate receptors in schizophrenia containing the GluR5 subunit would likely affect the 'fine-tuning' of both inhibitory and excitatory synaptic transmission in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Kainate receptor agonists have been either reported to increase (26,37) or have no effect on the frequency of mIPSCs (24). We tested the effect of the Ca 2ϩ uncaging on mIPSCs recorded in the presence of 0.5 M tetrodotoxin to block action potentials.…”
Section: Modulation Of Mipscs By Astrocytic Calcium Elevationmentioning
confidence: 99%
“…KARs have two major activities: they contribute to the excitatory postsynaptic current/potential in response to glutamate and modulate the release of neurotransmitters (␥-aminobutyric acid [GABA] and glutamate) through presynaptic action. [39][40][41] Moreover, KARs are subjected to developmental and activitydependant regulation 42 and GluR6 function is modulated by protein phosphorylation. 43 GluR6 is abundantly expressed in brain regions involved in learning and memory (such as the hippocampus) as well as in motor and motivational aspects of behaviour (such as basal ganglia and the cerebellum).…”
Section: Glur6 As a Genetic Factor In Autism?mentioning
confidence: 99%